Role of the Kidneys in Resistant Hypertension - Z. Khawaja; C. S. Wilcox (International Journal of Hypertension)
Resistant hypertension is a failure to achieve goal BP (<140/90 mm Hg for the overall population and <130/80 mm Hg for those with diabetes mellitus or chronic kidney disease) in a patient who adheres to maximum tolerated doses of 3 antihypertensive drugs including a diuretic. The kidneys play a critical role in long-term regulation of blood pressure. Blunted pressure natriuresis, with resultant increase in extracellular fluid volume, is an important cause of resistant hypertension. Activation of the renin-angiotensin-aldosterone system, increased renal sympathetic nervous system activity and increased sodium reabsorption are important renal mechanisms. Successful treatment requires identification and reversal of lifestyle factors or drugs contributing to treatment resistance, diagnosis and appropriate treatment of secondary causes of hypertension, use of effective multidrug regimens and optimization of diuretic therapy. Since inappropriate renal salt retention underlies most cases of drug-resistant hypertension, the therapeutic focus should be on improving salt depleting therapy by assessing and, if necessary, reducing dietary salt intake, optimizing diuretic therapy, and adding a mineralocorticoid antagonist if there are no contraindications.